Synthesis, characterization and antioxidant activity of 1,2,4-triazole and its Schiff base derivatives - Wong, Wen Li (2023)
1,2,4-Triazole and its Schiff base derivatives are found to exhibit diverse biological activities which could contribute to medicinal field as novel drugs. The synthesized novel 1,2,4-triazole and its Schiff base compounds were characterized for their antioxidant potential. The 1,2,4-triazole was synthesized by fusion reaction between indole-3-acetic acid and thiocarbohydrazide, while the Schiff bases were synthesized from the condensation reaction between 1,2,4-triazole and a series of benzaldehyde derivatives. The compounds were characterized using modern IR and NMR techniques for structure elucidation. The antioxidant activity of the synthesized compounds was determined using DPPH assay with BHT as standard antioxidant. 1,2,4-Triazole and its Schiff bases showed moderate antioxidant activities with IC50 ranged from 40.3 to 176.4 ppm, except for SBs 6, 7, 8, and 14, which showed IC50 more than 200 ppm which exceeded the concentration range prepared for the DPPH assay.